Efficient and consistent line simplification for web mapping. (16th January 2007) - Bertolotto, Michela; Zhou, Min
Commercial Geographical Information Systems (GISs) incorporate line simplification functionality to generate generalised versions of maps. A commonly used algorithm is the classical Ramer-Douglas-Peucker (RDP) algorithm. Such an algorithm does not guarantee the preservation of topological consistency and therefore requires a posteriori checks to rectify unwanted intersections. To overcome this problem, Saalfeld proposed a modification based on the fact that, while generalising a polyline, conflicts can only occur with vertices of other polylines that lie within its convex hull. We have developed an improved version of Saalfeld's algorithm to detect possible self-intersections more efficiently. Although this improves the performance, especially when generalising very large data sets, the processing time is still not acceptable for real-time web mapping. Therefore, we have integrated our algorithm into a web-mapping system that relies on progressive transmission. In this paper we describe our improved algorithm and the experimental results. We also discuss the progressive transmission approach.